A Simpler Method for Predicting Weight Loss in the First Year after Roux-en-Y Gastric Bypass - John P. Sczepaniak; Milton L. Owens; William Garner; Farouk Dako; Kristin Masukawa; Samuel E. Wilson (Journal of Obesity)
Factors postulated to predict weight loss after gastric bypass surgery, include race, age, gender, technique, height, and initial weight. This paper contained 1551 gastric bypass patients (85.9% female). Operations were performed by one surgeon (MLO) at community hospitals in Southern California from 1989 to 2008 with 314 being laparoscopic and 1237 open. We created the following equation: In[percent weight] =𝐴𝑡2−𝐵𝑡, where 𝑡 was the time after operation (days) and 𝐴 and 𝐵 are constants. Analysis was completed on R-software. The model fits with 𝑅2 value 0.93 and gives patients a realistic mean target weight with a confidence interval of 95% for the first year. Conclusion. We created a curve predicting weight loss after surgery as a percentage of initial weight. Initial weight was the single most important predictor of weight loss after surgery. Other recorded variables accounted for less than 1% of variability. Unknown factors account for the remaining 6-7%.